Epidemiological changes in oesophageal cancer at National Hospital, Bloemfontein: 1995, 2000 and 2005 - Tian van der Merwe; Ruan van der Walt; Jován Esterhuizen; Stephani Botha; Louis Goedhals; Gina Joubert (AOSIS, 2010)
Background: Oesophageal cancer is a common malignancy with a high mortality rate. The two main histological types are squamous cell and adenocarcinoma. An increase in oesophageal adenocarcinoma has been noted, especially in developed countries. Objectives: The aim of this retrospective study was to investigate the profile of oesophageal cancer by reviewing medical records of patients diagnosed with oesophageal cancer in 1995, 2000 and 2005. Method: The study sample consisted of 474 files of patients diagnosed, for the first time, with oesophageal cancer in 1995, 2000 and 2005, at the National Hospital in Bloemfontein and the outreach clinics in surrounding areas. Information reviewed from patient files included: age, race and gender of the patient, as well as topography, size, histological grade and type of the tumour. Results: The number of newly diagnosed cases of oesophageal carcinoma decreased over the 10-year period. The mean age of patients was > 57 years. The majority of cases were Black patients: 90.5% in 1995, 93.2% in 2000 and 87.7% in 2005. More male patients were seen (71.5% in 1995, 70.1% in 2000 and 64.2% in 2005), although the number of female patients diagnosed with this malignancy increased by 7.3% from 1995 to 2005. The mid- and lower third of the oesophagus were affected most commonly, most lesions were 6 cm - 10 cm in length and classified as Grade II, moderately differentiated tumours. Squamous cell carcinoma was diagnosed in 76.9% of patients in 1995, 90.5% in 2000 and 94.3% in 2005. Conclusion: The number of newly diagnosed cases of oesophageal carcinoma decreased over the 10-year period, but demographic and disease characteristics remained constant.